2016
DOI: 10.1080/19443994.2016.1157989
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of two-stage spiral wound forward osmosis elements at various operation conditions

Abstract: A B S T R A C TForward osmosis (FO) is an emerging process in water industry for wastewater treatment, water reuse, and desalination. Although many lab-scale studies have been done, the data generated cannot be directly applied to a real pilot plant due to different membrane configuration and operating conditions. In this study, we evaluated commercial spiral wound forward osmosis (SWFO) elements in various operating conditions (draw solution concentration, flow rate, and element array type). First, we investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 34 publications
1
8
1
Order By: Relevance
“…Unlike previously reported FO performance in lab-scale tests, it has been reported that the actual FO element performances in pilot-scale tests are strongly dependent on hydraulic pressure [12][13][14][15]. They found that, if the membranes are serially connected, a significant pressure build-up at the inlet (particularly in the draw inlet) arises [12]. This is a direct indication that the economics of PAFO-RO hybrid process is in close relation with the hydraulic pressure dependence of FO elements in series.…”
Section: Introductioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Unlike previously reported FO performance in lab-scale tests, it has been reported that the actual FO element performances in pilot-scale tests are strongly dependent on hydraulic pressure [12][13][14][15]. They found that, if the membranes are serially connected, a significant pressure build-up at the inlet (particularly in the draw inlet) arises [12]. This is a direct indication that the economics of PAFO-RO hybrid process is in close relation with the hydraulic pressure dependence of FO elements in series.…”
Section: Introductioncontrasting
confidence: 69%
“…There have been other attempts to evaluate the economic feasibility of the FO-RO hybrid, yet, with a limitation that the data sets were drawn from lab-scale tests employing small membrane coupons [8,11]. Unlike previously reported FO performance in lab-scale tests, it has been reported that the actual FO element performances in pilot-scale tests are strongly dependent on hydraulic pressure [12][13][14][15]. They found that, if the membranes are serially connected, a significant pressure build-up at the inlet (particularly in the draw inlet) arises [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, this can be reduced by increasing the cross-flow velocity (CFV) or adding a surfactant such as TWIN20. Higher CFVs can lessen the formation of CP layer, and adding surfactants can reduce viscosity and interaction between the polymers or between the membrane surface and polymers 6 8 . During the FO-LPM experiment, magnetic stirrer was used for reducing CP and permeate retention phenomenon by dilution.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the advantages offered by hybrid systems include lower energy consumption rates, higher rejection rates, lower fouling propensities and enhanced process efficiency (low operating costs, etc.) compared to single processes 3 , 8 , 9 . Still, operational costs, including the cost of energy and the maintenance issues inherent in membrane processes are some of the main limitations for stand in the water treatment industrial area.…”
Section: Introductionmentioning
confidence: 99%
“…A number of previous studies covered the analyses on element-based FO performance and, without exception, hydraulic pressure build-ups at the inlet and the associated hydraulic pressure drops (i.e. hydraulic pressure difference between the inlet and outlet of both feed and draw channels) occurred (Attarde, Jain, Chaudhary & Gupta, 2015;Im, Go, Lee, Park & Jang, 2016;Kim, Blandin, Phuntsho, Verliefde, Le-Clech & Shon, 2017;Kim & Park, 2011). The hydraulic pressure build-up at the inlet of the membrane element is the result of structural resistance of the water channel against the initial water flow input to the system.…”
Section: Practical Considerations For Implementing Fo Membranesmentioning
confidence: 99%